PENGARUH LEADER MEMBER EXCHANGE DAN EMPOWERMENT TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA - CEISA PUSPARINI, ATIKA (Jurnal Ilmu Manajemen (JIM), 2018)
Toll roads play an important role in driving the economy as a hub for people, goods and services. Leader member exchange and empowerment provided by superiors will improve job satisfaction and employee performance. This study uses a quantitative approach. The research was conducted on 191 operational employees of PT Jasa Marga (Persero) Tbk Branch of Surabaya Gempol. Sources of data used are primary and secondary data. This research using SEM analysis technique. The result shows that Leader Member Exchange has no effect on Job Satisfaction and Employee Performance, while Empowerment have positive and significant effect to Job Satisfaction and Employee Performance, Job Satisfaction has no effect on Employee Performance, and Job Satisfaction is not able to mediate influence Leader Member Exchange and Empowerment on Employee Performance.